The Influence of Discounts, Free Shipping, and Digital Advertising on Consumer Behavior in Online Shopping in East Jakarta - Rania Ayu Hanifah; Suparno; Siti Fatimah Zahra (Indo Publishing, 2025)
This study explores how promotional strategies namely discounts, free shipping, and digital advertising affect impulsive online shopping behavior among residents of RW 06, Makasar Sub-district, East Jakarta. From a population of 3,558 individuals, a random sample of 360 respondents was surveyed using structured questionnaires. The data were analyzed through descriptive-associative techniques, classical assumption testing, and multiple linear regression. The findings show that all three promotional factors together significantly influence consumer behavior. When examined separately, each factor also has a positive and significant effect, with discounts exerting the strongest impact, followed by free shipping and digital advertising. These results indicate that while promotional strategies effectively encourage online purchases, they can also lead to impulsive and less rational buying decisions. The study underscores the importance of implementing balanced promotional approaches and raising consumer awareness to support more thoughtful and sustainable shopping practices.